Emotional labour: a case study of secret recipe’s employees at Kota Bharu, Kelantan / Nurbaitie Natasha Mohd Ghani & Nurzatil Aqmar Mohd Wajiah - Mohd Wajiah, Nurzatil Aqmar; Mohd Ghani, Nurbaitie Natasha (Faculty of Hotel and Tourism, 2017)
In hospitality service industries, emotional labour is the exertion needed to give organisationally desired emotion during communication. It will give both positive and negative effect to organization and customer satisfaction. Employees who have failed to manage their emotion will give a negative effect to their company. It could lead to serious problems such as lack of employee morale and loss of their customers as employees play an important part in expanding business. All customers expect good service prepared for them. So, employees must have intention to fulfill their needs. Therefore, the objective of this study is to examine the level of acceptance of the emotional labour of Secret Recipe’s employees. In this research, there are three strategies that are studied further which are standard script, dress code and acting. Participation of questionnaire for this research is 60 respondents among six outlets of Secret Recipe’s employees in Kota Bharu, Kelantan. Data was gathered and analyzed by using SPSS version 19. Among the analysis used by the researcher are frequency analysis, descriptive analysis and reliability analysis. From the result, most of the staff agreed that all three strategies helped them in social skills and ability to communicate with customers and can guide employees to satisfy the customers. Besides that, they believe it can increase confidence level and social skills with their customers.